2020
DOI: 10.3390/coatings10040395
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Variable Viscosity Impact on MHD Flow and Heat Transfer of Nanofluid Using the Cattaneo–Christov Model

Abstract: In this mathematical study, magnetohydrodynamic, time-independent nanofluid flow over a stretching sheet by using the Cattaneo-Christov heat flux model is inspected. The impact of the thermal, solutal boundary and gravitational body forces with the effect of double stratification on the mass flow and heat transfer phenomena is also observed. The temperature-dependent viscosity impact on heat transfer through a moving sheet with capricious heat generation in nanofluids have studied, and the viscosity of the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The transformed set of nonlinear partial differential Equations (12)-(15) is solved numerically utilizing the variational finite element method along with boundary conditions (Equation (16)) because Equations (12)-(15) cannot be solved analytically due to highly nonlinearity. This procedure is a great numerical computational methodology significant for solving the different types of real word problems [44] and problems of engineering [45]-for example, liquids with heat transportation [46], Bio-materials [47], rigid body dynamics [48], and various regions [49,50]. An astounding general description of variational finite elements method outlined by Reddy [51] and Jyothi et al [52] summed up the basic steps involved in the FEM.…”
Section: Finite Element Methods Solutionsmentioning
confidence: 99%
“…The transformed set of nonlinear partial differential Equations (12)-(15) is solved numerically utilizing the variational finite element method along with boundary conditions (Equation (16)) because Equations (12)-(15) cannot be solved analytically due to highly nonlinearity. This procedure is a great numerical computational methodology significant for solving the different types of real word problems [44] and problems of engineering [45]-for example, liquids with heat transportation [46], Bio-materials [47], rigid body dynamics [48], and various regions [49,50]. An astounding general description of variational finite elements method outlined by Reddy [51] and Jyothi et al [52] summed up the basic steps involved in the FEM.…”
Section: Finite Element Methods Solutionsmentioning
confidence: 99%
“…is the relaxation time of particles phase, k is the Stoke's resistance (drag force), p c and s c are specific heat of fluid and dust particle, T and p T are the temperature of fluid and particle phases, T  is the thermal relaxation time, a is positive constant and s h is heat transfer parameter. It is important to note that, the viscosity,  considered herein follows the robust Reynold exponential model which can be defined as [39] ()…”
Section: T U U X Ax V H T Ymentioning
confidence: 99%
“…Gireesha et al [25] conducted an analysis of the magnetohydrodynamic boundary layer flow and the heat transfer of nanofluids over a flat stretching sheet. Several numerical studies have been reported to predict the characteristics of magnetized fluids, such as MHD mixed convection flows [26], MHD non-Newtonian fluid flows [27], MHD impact on nanofluid flows [28] and the magnetic dipole effects on micropolar fluid flows [29,30].…”
Section: Introductionmentioning
confidence: 99%